Skin Diseases Detection From Images - Amira, Lamrour; khadidja, Denidni; Supervisor: Roussafi, Mahdjoubi (Mohamed Boudiaf University of M'sila, 2025)
Many skin diseases are a big problem for public health since it can be hard to identify them early on. Some conventional diagnosis methods such as inspecting a patient, are not always perfect and may take a long time. Recent years have see impressive developments in artificial intelligence, especially in deep learning, helping to bring about new possibilities in medicine. In our study, a deep learning system is suggested to assist in spotting skin diseases early by studying skin images.
Keywords: Skin diseases; Machine learning; Healthcare; Health informatics; Deep leaning